1995
DOI: 10.1021/ac00097a020
|View full text |Cite
|
Sign up to set email alerts
|

Hologram-Based Thermooptical Absorbance Detection in Capillary Electrophoresis: Separation of Nucleosides and Nucleotides

Abstract: On-column thermooptical absorbance (TOA) detection in capillary electrophoretic separations of various nucleoside and mono-and diphosphate nucleotide mixtures absorbing at 257 nm is demonstrated in 20 fim i.d. capillaries. The analytes are optically pumped by a frequency-doubled argon ion laser and probed by a laser diode or by a He/ Ne laser beam guided to the detection volume by a holographic optical element Absorption detection limits of 2.2 //AU using time constants of 0.3 s and 20 mW of UV power are obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 20 publications
(1 reference statement)
3
16
0
Order By: Relevance
“…In recent years, due to the rapid developments of HPLC and CE separation techniques, a number of interference methods based on transmitted-beam interference [33][34][35] have been developed and successfully used as universal refractive index ͑RI͒ detection for HPLC and CE separations. Keeping other conditions the same, the retroreflected beam interference method is potentially more sensitive than the transmitted beam interference approach because the probe beam passes twice through the detection region in the retroreflected beam configuration.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, due to the rapid developments of HPLC and CE separation techniques, a number of interference methods based on transmitted-beam interference [33][34][35] have been developed and successfully used as universal refractive index ͑RI͒ detection for HPLC and CE separations. Keeping other conditions the same, the retroreflected beam interference method is potentially more sensitive than the transmitted beam interference approach because the probe beam passes twice through the detection region in the retroreflected beam configuration.…”
Section: Resultsmentioning
confidence: 99%
“…Methylated purine, pyrimidine and other modified nucleosides have been shown to be excreted in abnormal amounts in urine of patients with cancer (Watanabe and Maekawa, 2010;Hatziapostolou and Iliopoulos, 2011). Elevated concentrations have been suggested as possible markers of different forms and stages cancers (Hsu et al, 2011;Vareed et al, 2011;Markuszewski et al, 2010;Struck et al, 2011;Krattiger et al, 1995;Masuda et al, 1993) It was concluded that the levels of nucleosides in urine from cancer patients were, generally, elevated, and that the increase in modified nucleosides was more pronounced than that of normal nucleosides. In addition, the concentrations of pseudouridine (pseu), 1-methylinosine (m1I), N4-acetylcytidine (ac4C), 1-methylguanosine (m1G) and 2-methyl guanosine (m2G) in urine of cancer patients were elevated significantly.…”
Section: Analyses In Genomic Samplesmentioning
confidence: 99%
“…Micellar electrokinetic capillary chromatography (MEKC) has also been used for the determination of azidothymidine triphosphate [17] and nucleosides [8]. On-column thermo-optical absorbance detection has also been demonstrated in capillary electrophoretic separations of various nucleosides and nucleotides mixtures in MEKC modes [18]. A dynamic pH junction in CE for improved focusing of nucleotides has been introduced for improved concentration sensitivity [19].…”
Section: Introductionmentioning
confidence: 99%